Municipal amalgamations and local housing prices - Vifill Karlsson; Grétar þór EyÞórsson (REGION, 2022)
In this paper, we examine the relationship between housing prices and municipal amalgamations. Due to consumer preference for access over amenity value, there is a spatial disparity of housing prices, reflecting the value of land in specific locations. According to tiebout1956 local amenity values will increase if the services of a municipality improve without a comparable rise in taxes or service fees, or if taxes or service fees decrease while the service level remains the same. The bid-rent curve is a framework frequently used to capture a presence of goods or bads such as amenities, disamenities, and externalities. Accordingly, the present study will be used to detect a possible social benefit or loss following amalgamations of municipalities. Macro panel data from Iceland will be used, representing several essential variables of the house market for 79 municipalities in Iceland during the period from 1992 through 2006. The research shows a significant positive relationship, ceteris paribus, between regional municipal amalgamations and local real prices of apartments.
Keywords: 330; Housing prices; amalgamation of municipalities; Hedonic price model; localgovernment reforms; Fixed effect model